Preliminary assessment of methanogenic microbial communities in marine caves of Zakynthos Island (Ionian Sea, Greece) - POLYMENAKOU, PARASKEVI; MANDALAKIS, MANOLIS; DAILIANIS, THANOS; DIMITRIADIS, CHARALAMPOS; MEDVECKY, MATEJ; MAGOULAS, ANTONIOS; GEROVASILEIOU, VASILIS (Mediterranean Marine Science, 2018)
Mediterranean marine caves remain largely unexplored, while particularly limited information is available about the microbial life existing in these unique environments. The present study is a preliminary assessment of the composition of the active anaerobic microbial community colonizing the walls of newly explored systems of underwater caves and small cavities in Zakynthos Island. The interior of these caves is densely coated with egg-shaped, foam-shaped and filamentous biological structures that are characterised by a strong odor of hydrogen sulfide gas. A total of twelve structures scrapped from cave rocks were subjected to anaerobic cultivation for up to 208 days. Strong to moderate methanogenesis was observed in two different types of egg-shaped structures and one foam-like structure. Interestingly, this was observed in experiments that were performed at room temperature (i.e. 25oC) which is substantially lower than those typically considered optimum for methane production (e.g. 35oC). Analysis of the 16S rRNA genes revealed a clear dominance of archaea and bacteria closely related to known methane producers and sulfate reducers, including members of the families Methanomicrobiaceae, Desulfobulbaceae, Desulfobacteraceae, Desulfuromonaceae, Campylobacteraceae, Marinifilaceae, Clostridiaceae, Incertae Sedis – Family I & II. These results show that Mediterranean marine caves can host members of archaea and bacteria with potential biotechnological interest that deserve further investigation.